Intramolecular thermal stepwise [2 + 2] cycloadditions: investigation of a stereoselective synthesis of [n.2.0]-bicyclolactones. Issue 40 (20th September 2016) - Throup, Adam; Patterson, Laurence H.; Sheldrake, Helen M.
Abstract : A new method for the synthesis of highly functionalised cyclobutenes. Abstract : Fused cyclobutanes are found in a range of natural products and formation of these motifs in a straightforward and easy manner represents an interesting synthetic challenge. To this end we investigated an intramolecular variant of the thermal enamine [2 + 2] cyclisation, developing a diastereoselective intramolecular enamine [2 + 2] cyclisation furnishing δ lactone and lactam fused cyclobutenes in good yield and excellent diastereoselectivity.